Behavioral intention to use distance teaching in the pandemic era - Tseng, Chih-Hung; Wang, Ching-Tang; Hsu, Chin-Hsien; Liu, Jing-Wei (Frontiers in psychology, 2022)
This study aimed at exploring the impact of post-epidemic era on teachers’ behavioral intention of distance education. In this study, purposive sampling method was used to enroll 390 teachers in colleges and universities, high schools and vocational schools, and junior high and elementary schools to be the research subjects for the questionnaire survey. A total of 360 questionnaires were collected for statistics, and AMOS 23.0 statistical software was used to analyze the correlation between variables. Meanwhile, a structural equation model was used to analyze and verify the impact of the technology acceptance model, information system success model, and diffusion of innovations theory. According to the results, the system quality of distance teaching platforms certainly affected perceived usefulness, and perceived usefulness affected teachers’ attitudes toward using distance teaching systems. In addition, perceived ease of use had an impact on perceived usefulness, and trialability had an impact on teachers’ attitudes toward using distance teaching systems. Finally, teachers’ attitude toward using a distance teaching system also affected their behavioral intention. According to the results, suggestions were made in this study to teachers and students for distance teaching. Additionally, the main contribution of this study lies in providing specific strategies for further distance teaching through empirical results in combination with on-site teaching.